Solar cell, solar cell sheet and method for manufacturing the same
Patent Information
- Application Number
- CN202610902224.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-22
- Publication Date
- 2026-09-01
AI Technical Summary
其中,TOPCon太阳能电池片因制程导致的边缘微观结构缺陷(即边缘呈锯齿状),一方面容易使组件层压过程中因该缺陷处应力集中而导致裂纹失稳扩展,并最终引发电池片隐裂甚至出现碎片现象;另一方面,该结构缺陷会导致在该区域形成大量悬挂键和缺陷态,若损伤处(即暴露处)没有被钝化,会成为载流子(电子和空穴)的复合中心,加剧少子寿命衰减,造成效率损失,从而导致电池电性能降低
本发明提供的太阳电池片的受光面中,第二区域中金字塔数量为20500个/mm2~28500个/mm2,第一区域中金字塔数量为17000个/mm2~22500个/mm2,且第一区域的深度为0~15μm,曲率半径为1μm~200μm。满足上述特征的太阳电池片具有较为完整的边缘结构,微观结构缺陷少,一方面可缓解组件层压过程中因电池片边缘严重及大量的锯齿状结构的出现而产生的严重应力集中,实现应力的均匀分布,降低组件层压过程中裂纹失稳扩散并最终导致电池片隐裂的风险,从而有利于提升电池片的良率及可靠性;另一方面,可降低复合速率,利于后续钝化膜层的沉积,进一步改善电池片钝化性能。
Smart Images

Figure CN122679754A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solar cell technology, and more specifically, to a solar cell, a solar cell wafer, and a method for preparing the same. Background Technology
[0002] Against the backdrop of ever-growing global demand for clean energy, solar energy, as a sustainable and clean energy source, has received widespread attention. TOPCon cells, as a new generation of photovoltaic solar cells, have become the focus of the photovoltaic industry due to their high photoelectric conversion efficiency.
[0003] Although TOPCon solar cells have achieved high photoelectric conversion efficiency, some issues still hinder further efficiency gains. Among these, microstructural defects at the edges of TOPCon solar cells caused by the manufacturing process (i.e., serrated edges) can easily lead to stress concentration during module lamination, causing unstable crack propagation and ultimately resulting in microcracks or even cell fragmentation. Furthermore, these structural defects can lead to the formation of numerous dangling bonds and defect states in the affected area. If the damaged areas (i.e., exposed areas) are not passivated, they become recombination centers for charge carriers (electrons and holes), exacerbating minority carrier lifetime decay, causing efficiency loss, and ultimately reducing the cell's electrical performance.
[0004] In view of this, the present invention is proposed. Summary of the Invention
[0005] The purpose of this invention is to provide a solar cell, a solar cell wafer, and a method for preparing the same, in order to solve or improve the above-mentioned technical problems.
[0006] This invention can be implemented as follows: In a first aspect, the present invention provides a solar cell, the solar cell comprising a light-receiving surface and a back-lighting surface disposed opposite to each other, the light-receiving surface having a pyramidal textured structure and the back-lighting surface having a polished pyramidal base structure. The light-receiving surface includes a first region and a second region; The second region is located in the middle of the light-receiving surface, and the number of pyramids in the second region is S2, where S2 is 20,500 pyramids / mm. 2 ~28,500 pieces / mm 2 ; The first region is connected to the second region and is located outside the second region; the number of pyramids in the first region is S1, and S1 is 17,000 / mm. 2 ~22,500 pieces / mm 2 The depth of the first region is H1, which is 0~15μm; the radius of curvature of the first region is ρ, which is 1μm~200μm.
[0007] In an optional implementation, the stress concentration factor of the first region is Kt, Kt=1+ .
[0008] In an optional implementation, Kt is 1.06 to 7.32.
[0009] Secondly, the present invention provides a method for preparing a solar cell as described in any of the foregoing embodiments, comprising the following steps: removing PSG from a silicon wafer, alkaline washing, first water washing, acid washing, and second water washing.
[0010] In an optional implementation, during the PSG removal process, the relative velocity between the silicon wafer and the etching solution is V. k V k =3.85m / s~10.5m / s.
[0011] In an optional implementation, during the PSG removal process, the concentration of HF in the etching solution is C. k C k =40wt%~76wt%.
[0012] In an optional embodiment, during alkaline washing, the concentration of alkali in the alkaline solution is Q. k =36.75wt%~78wt%.
[0013] In an optional embodiment, the reaction temperature during alkaline washing is T. k T k =51℃~79.2℃.
[0014] In an optional embodiment, the above preparation method further includes the following steps: depositing a passivation layer on the surface of the battery cell after a second water wash, followed by wire mesh sintering.
[0015] Thirdly, the present invention provides a solar cell comprising at least one solar cell of the aforementioned embodiments.
[0016] The beneficial effects of this invention include: In the solar cell provided by this invention, the number of pyramids in the second region is 20,500 per mm. 2 ~28,500 pieces / mm 2 The number of pyramids in the first region is 17,000 / mm. 2 ~22,500 pieces / mm 2Furthermore, the depth of the first region is 0~15μm, and the radius of curvature is 1μm~200μm. Solar cells that meet the above characteristics have relatively complete edge structures and fewer microstructural defects. On the one hand, this can alleviate the severe stress concentration caused by the severe edge and numerous serrated structures of the cell during module lamination, achieve uniform stress distribution, and reduce the risk of crack instability and propagation during module lamination, which may ultimately lead to microcracks in the cell, thereby improving the yield and reliability of the cell. On the other hand, it can reduce the recombination rate, which is beneficial for the subsequent deposition of the passivation film layer and further improves the passivation performance of the cell. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 This is a microstructure diagram of the edge of the solar cell provided in Example 1. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0020] The solar cell, solar cell wafer, and their preparation method provided by the present invention will be described in detail below.
[0021] The present invention provides a solar cell comprising a light-receiving surface and a back-lighting surface arranged opposite to each other. The light-receiving surface has a pyramidal textured structure, and the back-lighting surface has a polished pyramidal base structure.
[0022] The light-receiving surface includes a second region and a first region arranged sequentially from its center to its edge, and the first region is connected to the second region. That is, the second region is located in the middle part of the light-receiving surface, and the first region is connected to the second region and located outside the second region.
[0023] The number of pyramids in the first region is S1, and S1 is 17,000 / mm. 2 ~22,500 pieces / mm 2 For example, 17,000 pieces / mm 2 18,000 pieces / mm 2 19,000 pieces / mm 220,000 pieces / mm 2 21,000 pieces / mm 2 22,000 pieces / mm 2 Or 22,500 pieces / mm 2 Alternatively, it can be 17,000 pieces / mm. 2 ~22,500 pieces / mm 2 Other values within the range.
[0024] The number of pyramids in the second region is S2, and S2 is 20,500 / mm. 2 ~28,500 pieces / mm 2 For example, 20,500 pieces / mm 2 21,000 pieces / mm 2 22,000 pieces / mm 2 23,000 pieces / mm 2 24,000 pieces / mm 2 25,000 pieces / mm 2 26,000 pieces / mm 2 27,000 pieces / mm 2 28,000 pieces / mm 2 Or 28,500 pieces / mm 2 Alternatively, it can be 20,500 pieces / mm. 2 ~28,500 pieces / mm 2 Other values within the range.
[0025] In this invention, the first region of the solar cell is located at the edge of the light-receiving surface, and the second region is located in the middle of the light-receiving surface. The number of pyramids S1 in the first region is set to 17,000 per mm. 2 ~22,500 pieces / mm 2 This makes it lower than the number of pyramids S2 in the second region (20,500 / mm). 2 ~28,500 pieces / mm 2 This reduces the specific surface area of the first region. As a result, a thicker film can be formed in the first region during subsequent film deposition. Simultaneously, during the cleaning process, the smaller specific surface area of the first region prevents over-corrosion, thus preventing jagged defects at its edges. The second region, retaining a greater number of pyramidal structures, effectively reduces the reflectivity of the solar cell's light-receiving surface, improving light absorption efficiency.
[0026] In some optional embodiments, the depth of the first region is H1, which can be 0~15μm, such as 0μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, or 15μm, or other values within the range of 0~15μm. In some more typical embodiments, H1 is 4.5μm~14μm.
[0027] In this article, the "depth H1 of the first region" is defined as the depth of the first region, starting from any point (denoted as point A) on an edge of the first region that is close to the second region. A perpendicular line is drawn along this point, eventually intersecting the edge of the first region that is far from the center of the solar cell. The intersection point is denoted as point B. The length between point A and point B is the depth of the first region.
[0028] If H1 is greater than 15μm, it indicates that there are too many microstructural defects at the edge, which can easily cause stress concentration at the defect and lead to unstable crack propagation. In addition, it can also lead to the formation of a large number of dangling bonds and defect states in this region, resulting in efficiency loss.
[0029] In some optional embodiments, the radius of curvature of the first region is ρ, which can be 1 μm to 200 μm, such as 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 50 μm, 100 μm, 150 μm, or 200 μm, or other values within the range of 1 μm to 200 μm. In some more typical embodiments, ρ is 20 μm to 140 μm.
[0030] In this paper, "radius of curvature ρ of the first region" refers to the local radius of curvature at the sawtooth or arc-shaped microstructure at the edge of the light-receiving surface of the solar cell (i.e., the first structural region).
[0031] The aforementioned larger radius of curvature helps ensure that when external forces (such as lamination pressure) are applied, the stress is not infinitely amplified at a tiny sharp point on the edge, but is smoothly distributed over a larger area, thus effectively suppressing crack initiation and propagation. However, if the radius of curvature ρ is greater than 200 μm, it is not conducive to forming an effective morphological buffer transition in the edge region, and it is easy to cause abrupt stress concentration at the interface between the first and second regions, which increases the risk of microcrack initiation during lamination.
[0032] In some alternative implementations, the stress concentration factor of the first region is Kt, Kt=1+ Where H1 is 0~15μm and ρ is 1μm~200μm. In some typical embodiments, Kt is 1.06~7.32, and can be further 1.36~2.67.
[0033] By combining H1 and ρ in this application to obtain a reasonable stress concentration factor, it is beneficial to uniformly disperse edge stress during module lamination, avoiding crack instability and propagation caused by local stress concentration. It also facilitates the uniform deposition of the subsequent passivation film and reduces the edge recombination rate. Specifically, Kt, ranging from 1.06 to 7.32, further helps to achieve a good balance between suppressing edge microcracks and ensuring the structural integrity of the solar cell, thereby improving the yield and reliability of the solar cell.
[0034] In some alternative implementations, the side of the first region furthest from the center of the battery cell is serrated or arc-shaped, preferably arc-shaped.
[0035] Building upon the above, this invention optimizes the edge morphology of the solar cell, effectively controlling the serrated structure at the cell edges and making the edges relatively smooth and flat. On the one hand, this can alleviate the severe stress concentration caused by the presence of numerous serrated structures at the cell edges during module lamination, achieving uniform stress distribution and reducing the risk of crack instability and propagation during module lamination, ultimately leading to microcracks in the cell, thus improving the yield and reliability of the solar cell. On the other hand, compared with solar cells with numerous and large serrated edge structures produced by traditional processes (serrated edges are often accompanied by numerous dangling bonds and lattice damage, these areas are rapid recombination centers for charge carriers), this invention can significantly reduce the edge defect state density and reduce the recombination rate. At the same time, the smooth edge structure is also conducive to the subsequent deposition of passivation film layers, further improving the passivation performance of the solar cell.
[0036] Accordingly, the present invention also provides a method for preparing the above-mentioned solar cell, comprising the following steps: removing PSG from the silicon wafer, alkaline washing, first water washing, acid washing, and second water washing.
[0037] In some alternative implementations, during the PSG removal process, the relative velocity between the silicon wafer and the etching solution is V. k V k =3.85m / s~10.5m / s, for example, V k It can be 3.85m / s, 4m / s, 5m / s, 6m / s, 7m / s, 8m / s, 9m / s, 10m / s or 10.5m / s, or other values within the range of 3.85m / s to 10.5m / s.
[0038] This invention uses V k Controlling the velocity to 3.85 m / s~10.5 m / s helps retain an appropriate amount of PSG layer at the edge of the solar cell, thus effectively protecting the edge structure during subsequent alkaline washing, reducing the depth of the serrated edge structure, and suppressing the occurrence of numerous serrated defects. However, if V kA speed greater than 10.5 m / s can easily lead to over-corrosion of the PSG layer, causing the edges to lose protection and become excessively corroded by the chemical solution during alkaline washing. This can exacerbate the serrated defect structure at the edges and even increase the risk of edge damage or microcracks.
[0039] In some alternative implementations, during the PSG removal process, the etching solution is primarily composed of HF and water, with the HF concentration in the etching solution being C. k C k =40wt%~76wt%, for example, C k It can be 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, or 76wt%, or other values within the range of 40wt% to 76wt%.
[0040] This invention uses C k Controlling the concentration to 40wt%~76wt% helps maintain an appropriate PSG layer thickness at the cell edges, reducing excessive corrosion of the edge silicon substrate by the chemical solution during subsequent alkaline washing, thereby reducing the depth of the edge serrated structure and suppressing the generation of numerous serrated defects. However, if C k If the PSG layer is less than 40wt%, it is easy to cause insufficient removal of the PSG layer and excessive PSG residue at the edges, which can lead to leakage in the solar cell and affect its electrical performance.
[0041] Building upon the above, this invention optimizes the relative speed between the silicon wafer and the etching solution, as well as the HF concentration in the etching solution, during the PSG removal process. This allows a certain thickness of PSG layer to be retained at the edge of the solar cell, reducing excessive corrosion of the cell edge by the etching solution during the RCA alkaline bath reaction. This reduces the depth of the serrated edge structure while suppressing the formation of numerous serrated edges. The aforementioned PSG mainly consists of silicon oxide, along with some incompletely reacted phosphorus pentoxide and phosphorus atoms. The slow reaction rate of silicon oxide with alkali helps protect the solar cell edge (silicon) from excessive corrosion in the alkaline bath, mitigating or suppressing the formation of serrated structures.
[0042] In some optional embodiments, during alkaline washing, the alkaline solution is mainly formed from alkali and water, and the concentration of alkali in the alkaline solution is Q. k Q k =36.75wt%~78wt%, for example, Q k It can be 36.75wt%, 40wt%, 50wt%, 60wt%, 70wt%, 75wt%, or 78wt%, or other values within the range of 36.75wt% to 78wt%.
[0043] This invention uses Q kThe alkaline solution, controlled at a concentration of 36.75wt%~78wt%, exhibits a tip-priority etching characteristic on silicon. This effect both smooths out peaks and fills in valleys, transforming the edge morphology of the solar cell from a sharp, serrated shape to a smoother, flatter structure, thus improving cell performance. The smoothing of peaks is primarily due to the presence of numerous sharp protrusions and depressions in serrated edges. These protrusions have higher surface energy and faster reaction rates, and in a high-concentration alkaline solution, these protrusions are preferentially and rapidly etched away. Filling in valleys is mainly because the increased local concentration of reaction products (silicates) forms a temporary protection at the depressions, slowing further etching at the bottom of the valleys. However, if Q... k If the etching rate is greater than 78 wt%, it can easily lead to excessive etching of the edge silicon substrate by the alkaline solution, making the edge structure too smooth or even causing local depressions or thinning. At the same time, excessive etching may damage the integrity of the edge surface, affecting the uniform deposition of the subsequent passivation film layer, which is not conducive to the stable output of the battery's electrical performance.
[0044] In some alternative embodiments, the reaction temperature during alkaline washing is T. k T k =51℃~79.2℃, for example, T k It can be 51℃, 55℃, 60℃, 65℃, 70℃, 75℃ or 79.2℃, or other values within the range of 51℃ to 79.2℃.
[0045] This invention uses T k Maintaining the temperature between 51℃ and 79.2℃ can prevent the edge areas from being "over-eaten" and forming jagged edges due to excessively rapid reaction. However, if T... k Temperatures below 51°C can easily lead to an excessively low alkaline washing reaction rate, making it impossible to effectively smooth and round the serrated edge structure. This results in poor improvement of edge stress concentration and recombination centers, and may even leave sharp serrations due to insufficient reaction, which is not conducive to reducing the risk of microcracks and improving battery performance.
[0046] In some optional embodiments, the alkaline washing time can be 250s to 500s, such as 250s, 300s, 350s, 400s, 450s or 500s, or other values within the range of 250s to 500s.
[0047] In some optional embodiments, the temperature of the first water wash can be 68℃~78℃, such as 68℃, 70℃, 72℃, 75℃, or 78℃, or other values within the range of 68℃~78℃. The duration of the first water wash can be 80s~150s, such as 80s, 100s, 120s, or 150s, or other values within the range of 80s~150s.
[0048] In some optional embodiments, the pickling temperature can be 68℃~78℃, such as 68℃, 70℃, 72℃, 75℃, or 78℃, or other values within the range of 68℃~78℃. The pickling solution during the pickling process consists of HF and water, and the concentration of HF can be 0.1wt%~0.5wt%, such as 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, or 0.5wt%, or other values within the range of 0.1wt%~0.5wt%. The pickling time can be 300s~550s, such as 300s, 350s, 400s, 450s, or 500s, or other values within the range of 300s~550s.
[0049] In some optional embodiments, the temperature of the second wash can be 68℃~78℃, such as 68℃, 70℃, 72℃, 75℃, or 78℃, or other values within the range of 68℃~78℃. The duration of the second wash can be 80s~150s, such as 80s, 100s, 120s, or 150s, or other values within the range of 80s~150s.
[0050] Furthermore, the above preparation method may also include the following steps: depositing a passivation layer on the surface of the battery cell after the second water washing, followed by wire mesh sintering.
[0051] In some alternative implementations, the battery cells after the second water wash can be lifted and dried, then a passivation layer can be deposited and wire-sintered.
[0052] In some alternative implementations, the lifting speed can be 1 mm / s to 4 mm / s, such as 1 mm / s, 2 mm / s, 3 mm / s or 4 mm / s, or other values within the range of 1 mm / s to 4 mm / s.
[0053] In some alternative embodiments, the drying temperature can be 80°C to 95°C, such as 85°C, 90°C, or 95°C, or other values within the range of 80°C to 95°C. The drying time can be 10 min to 20 min, such as 10 min, 15 min, or 20 min, or other values within the range of 10 min to 20 min.
[0054] It should be noted that the PSG, alkaline washing, first water washing, acid washing, second water washing, preparation of the passivation layer, and other conditions involved in wire mesh sintering in this invention can all be found in the relevant prior art, and will not be elaborated on here.
[0055] As described above, the preparation method provided by this invention can maintain or improve the electrical performance of the battery, protect the integrity of the edge structure, suppress edge recombination, and significantly reduce the occurrence of microcracks during the module lamination process. This helps to ensure the normal output of the excellent electrical performance of the battery cells, so that the battery efficiency and module power are in one-to-one correspondence.
[0056] In addition, the present invention also provides a solar cell comprising at least one of the aforementioned solar cells.
[0057] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0058] Example 1 This embodiment provides a solar cell comprising a light-receiving surface and a back-lighting surface arranged opposite to each other. The light-receiving surface has a pyramidal textured structure, and the back-lighting surface has a polished pyramidal base structure. The light-receiving surface includes a second region and a first region that are sequentially arranged and connected from its center to its edge.
[0059] The number of pyramids in the first region is S1, and S1 is 20,000 / mm. 2 The number of pyramids in the second region is S2, and S2 is 24,000 / mm. 2 The depth of the first region is H1, which is approximately 5.1 μm; the radius of curvature of the first region is ρ, which is approximately 120 μm. The stress concentration factor of the first region is Kt, which is 1.41.
[0060] The microstructure diagram of the edge of the solar cell is shown below. Figure 1 As shown in the figure (from top to bottom, the marked areas are 4.40μm and 2.59μm respectively), it can be seen from the figure that: the first region of the edge of the solar cell has a smooth arc-shaped structure without obvious sharp serrations; the edge contour is flat and continuous, with a large radius of curvature, shallow depth, and small stress concentration factor.
[0061] The above-mentioned method for preparing solar cells may include the following steps: removing PSG from silicon wafers, alkaline washing, first water washing, acid washing, second water washing, pulling, drying, followed by surface passivation layer deposition and wire mesh sintering.
[0062] During the PSG removal process, the relative velocity between the silicon wafer and the etching solution is V. k V k =7.18 m / s. During PSG removal, the concentration of HF in the etching solution is C. k C k =58%.
[0063] During alkaline washing, the concentration of alkali in the alkaline solution is Q. k Q k=57.375wt%. The reaction temperature during alkali washing is T. k T k =65℃. Alkali washing time is 350s.
[0064] The temperature of the first water wash was 73℃, and the time was 120 seconds.
[0065] The pickling temperature was 73℃, the HF concentration during the pickling process was 0.3wt%, and the pickling time was 420s.
[0066] The second wash was performed at a temperature of 73℃ for 120 seconds.
[0067] The lifting speed is 2mm / s.
[0068] The drying temperature is 88℃ and the time is 15 minutes.
[0069] Example 2 The difference between this embodiment and Embodiment 1 is that the number of pyramids in the first region is S1, and S1 is 17,000 / mm. 2 The number of pyramids in the second region is S2, and S2 is 20,500 / mm. 2 The depth of the first region is H1, which is approximately 4.5 μm; the radius of curvature of the first region is ρ, which is approximately 140 μm. The stress concentration factor of the first region is Kt, which is approximately 1.36.
[0070] The fabrication method of this solar cell is the same as in Example 1, except that: during the PSG removal process, the relative velocity between the silicon wafer and the etching solution is V. k V k =10.5 m / s. During the PSG removal process, the concentration of HF in the etching solution is C. k C k =40%.
[0071] During alkaline washing, the concentration of alkali in the alkaline solution is Q. k Q k =36.75wt%. The reaction temperature during alkali washing is T. k T k =51℃. Alkali washing time is 350s.
[0072] Example 3 The difference between this embodiment and Embodiment 1 is that the number of pyramids in the first region is S1, and S1 is 22,500 pyramids / mm. 2 The number of pyramids in the second region is S2, and S2 is 28,500 / mm. 2The depth of the first region is H1, which is approximately 14.0 μm; the radius of curvature of the first region is ρ, which is approximately 20 μm. The stress concentration factor of the first region is Kt, which is approximately 2.67.
[0073] The fabrication method of this solar cell is the same as in Example 1, except that: during the PSG removal process, the relative velocity between the silicon wafer and the etching solution is V. k V k =3.85 m / s. During the PSG removal process, the concentration of HF in the etching solution is C. k C k =76%.
[0074] During alkaline washing, the concentration of alkali in the alkaline solution is Q. k Q k =78wt%. During alkali washing, the reaction temperature is T. k T k =79.2℃. Alkali washing time is 350s.
[0075] Comparative Example 1 The difference between this comparative example and Example 1 is that: V k =1.05m / s.
[0076] The number of pyramids in the first region of this comparative example is S1, and S1 is 23,500 / mm. 2 The number of pyramids in the second region is S2, and S2 is 23,500 / mm. 2 The depth of the first region is H1, which is 18.6 μm; the radius of curvature of the first region is ρ, which is 0.5 μm. The stress concentration factor of the first region is Kt, which is 9.85.
[0077] Compared with Example 1, the edge structure of this comparative example is significantly smoother, which is beneficial for achieving uniform stress distribution during component lamination and reducing the risk of microcracks.
[0078] Comparative Example 2 The difference between this comparative example and Example 1 is that: V k =15m / s.
[0079] Comparative Example 3 The difference between this comparative example and Example 1 is that: C k =20%.
[0080] Comparative Example 4 The difference between this comparative example and Example 1 is that: C k =85%.
[0081] Comparative Example 5 The difference between this comparative example and Example 1 is that: Q k=20wt%.
[0082] Comparative Example 6 The difference between this comparative example and Example 1 is that: Q k =89wt%.
[0083] Comparative Example 7 The difference between this comparative example and Example 1 is that: T k =40℃.
[0084] Test case (1) The number of pyramids and the depth, radius of curvature and stress concentration factor of the first region of the battery cells prepared in Examples 1-3 and Comparative Example 1 were compared.
[0085] The number of pyramids was counted using a 3D Zeta microscope.
[0086] The depth of the first region was measured using a 3D Zeta microscope, the radius of curvature was measured using a 3D Zeta microscope, and the stress concentration factor was determined using Kt=1+ Calculated.
[0087] The results are shown in Table 1.
[0088] Table 1 Comparison Results
[0089] (2) Microcracks were compared between the solar cells prepared in Examples 1-3 and Comparative Examples 1-7. Specifically, each solar cell was laminated in a laminator at 145°C and a vacuum of -0.1MPa using a conventional module lamination process (laminating solar cells with encapsulation materials such as EVA and backsheet). The microcrack incidence rate during the lamination process was compared. Microcracks were identified by detecting dark lines or dark areas on the solar cells after lamination using an electroluminescence (EL) tester. The results are shown in Table 2.
[0090] Table 2 Test Results
[0091] As can be seen from Table 2, the battery cells of the present invention have a significantly lower microcrack rate.
[0092] (3) The electrical performance of the solar cells prepared in Example 1 and Comparative Examples 1-7 was tested using the Wavelabs solar simulator. The test conditions were: AM1.5, 1000W / m 2The test environment temperature was 25℃. Before the test, the light source was calibrated to simulate sunlight intensity using a standard silicon cell. The open-circuit voltage (Voc), short-circuit current (Jsc), fill factor (FF), and photoelectric conversion efficiency (Eff) of the corresponding solar cells were recorded, and the results are shown in Table 3.
[0093] Table 3 Test Results
[0094] As can be seen from Table 3, the solar panel prepared in Example 1 of this invention has better electrochemical performance than the solar panel prepared in the comparative example.
[0095] In summary, the preparation method provided by this invention enables solar cells to have a relatively complete edge structure and fewer microstructural defects. On the one hand, it can alleviate the severe stress concentration caused by the presence of severe and numerous serrated structures at the edges of the cells during the module lamination process, achieve uniform stress distribution, and reduce the risk of crack instability and propagation during module lamination, which may ultimately lead to microcracks in the cells, thereby improving the yield and reliability of the cells. On the other hand, it can reduce the recombination rate, which is beneficial for the subsequent deposition of passivation films and further improves the passivation performance of the cells.
[0096] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A solar cell, characterized in that, The solar cell includes a light-receiving surface and a back-lighting surface arranged opposite to each other. The light-receiving surface has a pyramidal textured structure, and the back-lighting surface has a polished pyramidal base structure. The light-receiving surface includes a first region and a second region; The second region is located in the middle part of the light-receiving surface, and the number of pyramids in the second region is S2, where S2 is 20,500 pyramids / mm. 2 ~28,500 pieces / mm 2 ; The first region is connected to the second region and is located outside the second region; the number of pyramids in the first region is S1, where S1 is 17,000 / mm. 2 ~22,500 pieces / mm 2 The depth of the first region is H1, where H1 is 0~15μm; the radius of curvature of the first region is ρ, where ρ is 1μm~200μm.
2. The solar cell according to claim 1, characterized in that, The stress concentration factor in the first region is Kt, Kt=1+ .
3. The solar cell according to claim 2, characterized in that, Kt ranges from 1.06 to 7.
32.
4. A method for preparing a solar cell as described in any one of claims 1 to 3, characterized in that, Includes the following steps: The silicon wafers are subjected to PSG removal, alkaline washing, first water washing, acid washing, and second water washing.
5. The preparation method according to claim 4, characterized in that, During the PSG removal process, the relative velocity between the silicon wafer and the etching solution is V. k V k =3.85m / s~10.5m / s.
6. The preparation method according to claim 4, characterized in that, During the PSG removal process, the concentration of HF in the etching solution is C. k C k =40wt%~76wt%.
7. The preparation method according to claim 4, characterized in that, During alkaline washing, the concentration of alkali in the alkaline solution is Q. k Q k =36.75wt%~78wt%.
8. The preparation method according to claim 4, characterized in that, During alkaline washing, the reaction temperature is T. k T k =51℃~79.2℃.
9. The preparation method according to claim 4, characterized in that, It also includes the following steps: A passivation layer is deposited on the surface of the battery cells after the second water wash, followed by wire mesh sintering.
10. A solar cell, characterized in that, It includes at least one solar cell as described in any one of claims 1 to 3.